Physician awareness and understanding of hereditary angioedema: A web‐based study in Japan - Atsushi Fukunaga; Miwa Kishimoto; Akinori Oh; Takeshi Akiyama; Ippei Kotera; Yoichi Inoue; Junichi Maehara (Frontiers Media S.A., 2022)
Abstract Objectives Hereditary angioedema (HAE) is a rare disease with acute attacks in the skin and mucosa throughout the body including life‐threatening laryngeal edema and abdominal attacks with severe pain. Physicians, regardless of specialty, may encounter HAE patients in their daily practice; however, low disease awareness may attribute to a considerable number of undiagnosed HAE patients in Japan. This study aims to identify issues associated with the diagnosis processes of HAE and to determine levels of HAE awareness among Japanese physicians from various specialties. Methods A web‐based quantitative survey was conducted using a physicians panel. Physicians from the following departments were included in the survey: internal medicine, dermatology, pediatrics, emergency medicine, and gastroenterological surgery. Results The proportions of physicians in dermatology, pediatrics, emergency medicine, internal medicine, and gastroenterological surgery who were able to select the C1‐INH activity test as a diagnosis test for potential HAE patients were 71.8%, 59.7%, 57.1%, 40.3%, and 25.7%, respectively. Multivariate analysis showed significant association between physicians who selected "strongly suspected" AE based on the case‐scenario and physicians who had knowledge of the essential HAE symptoms (laryngeal edema, swelling after tooth extraction, swelling of the tongue, and abdominal pain). Conclusions This study showed that disease awareness of HAE varied among medical specialties, suggesting the importance of educational activities in academic societies and specialist accreditation in raising HAE awareness. Proper knowledge of complement testing and HAE symptoms may help not only to diagnose patients with AE‐like symptoms as AE but also to differentially diagnose HAE from AE.